The Place and Role of Statistics in Economic Research (on the Example of Banking Analysis) - GERASYMENKO, S. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The article considers the place and role of statistics in economic research in general, and in more detail - in banking research. A brief overview of the formation of the basic principles of economic statistics and the tasks of economic research, which are solved with its help. With reference to the opinions of prominent scientists, it is proved that statistics on the structure of construction and tasks that can be solved is a science, not a method of analysis. Attention is drawn to the need for clear formulation of the purpose and objectives of the study to obtain results, the use of which will contribute to the development of effective management decisions, in particular in banking. The use of statistical indicators and methods in assessing the risks of banking is considered in detail. In particular, the positive and negative factors of such assessment using the VaR-methodology were identified and the reasons that hinder its implementation in the practice of commercial banks of Ukraine were pointed out. To increase the reliability of the results of comparative analysis, which should help reduce the risks of banking, a number of statistical methods have been proposed. It is substantiated that multidimensional estimates, which, in particular, provide regression analysis, are the most suitable for comprehensive generalization of banking results. Conclusions on the directions of using the results of statistical observations in the management of the bank are formulated.